Pengaruh Kompetensi, Kompleksitas dan Workload terhadap Kualitas Audit dengan Pemahaman Sistem Informasi Sebagai Variabel Moderasi - Atta Putra Harjanto; Siti Rahayu Lorosae Murianingsih; Sri Harjanto; Armania Putri Wardhani (Jurnal Ekonomi Manajemen Akuntansi, 2024)
Purpose: The purpose of this study is to analyze the Influence of Competence, Complexity, Workload on Audit Quality. In addition, this study is to determine whether or not there is a role of understanding information systems in moderating the influence of Competence, Complexity, Workload on Audit Quality. Method: The population in this study were auditors working in Public Accounting Firms in Semarang City. The research sample used a purposive sampling technique. The data collection technique was distributing questionnaires to 15 KAPs in Semarang City, with a note that 11 KAPs were willing to fill out the questionnaire while 4 KAPs refused to fill out the questionnaire. The analysis tool used was IBM SPSS Statistics 23. Findings: The results of the study prove that competence has a significant negative effect on audit quality, complexity and workload do not affect audit quality. Meanwhile, understanding information systems can moderate by strengthening the influence of competence on audit quality and understanding information systems can moderate by weakening the influence of complexity and workload on audit quality. Novelty: In this study, previous studies have not found involvement in competence, complexity, and workload that have an effect on audit quality. So the author is interested in researching more deeply about the factors that influence audit quality by presenting a moderating variable, namely understanding of information systems.